1997
DOI: 10.1016/s0969-2126(97)00254-2
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the cofactor-binding fragment of the LysR family member, CysB: a familiar fold with a surprising subunit arrangement

Abstract: The overall structure of CysB(88-324) is strikingly similar to those of the periplasmic substrate-binding proteins. A similar fold has also been observed in the cofactor-binding domain of Lac repressor, implying a structural relationship between the Lac repressor and LysR families of proteins. In contrast to Lac repressor, in CysB the twofold axis of symmetry that relates the monomers in the dimer is perpendicular rather than parallel to the long axis of the cofactor-binding domain. This seems likely to place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 42 publications
4
106
0
1
Order By: Relevance
“…Examples of structure solutions using the dm program and a multi-crystal version include the GTPase-activating domain from p50rhoGAP (Barrett et al, 1997), and the cofactor-binding fragment of the LysR family member CysB (Tyrrell et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of structure solutions using the dm program and a multi-crystal version include the GTPase-activating domain from p50rhoGAP (Barrett et al, 1997), and the cofactor-binding fragment of the LysR family member CysB (Tyrrell et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that WT CysB is a tetramer, the trans-dominance of the multicopy CysB mutant forms may be explained by titration of WT CysB monomers and formation of inactive mixed heterooligomers. Therefore, it seems that none of the mutations altering residues 11,20,22,160,196,244, and 247 abolished the oligomerization ability of CysB. In contrast, CysB variants E41K, L44R, and I48T expressed from plasmids did not confer the Cys Ϫ phenotype to the EC1250 strain and had no effect on expression of the cysBЈ::ЈlacZ fusion in the pMH303-containing EC1250 strain (Table II).…”
Section: Isolation and Initial Characterization Of Random Cysbmentioning
confidence: 97%
“…According to the structural model of the CysB dimer (20), 33 C-terminal amino acids (positions 292-324) form the loop exposed to the surface containing two helices. Therefore, this domain might be important for the overall structure of the native CysB molecule and its function.…”
Section: Isolation and Initial Characterization Of Random Cysbmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed of a DNA-binding domain and a cofactor-binding domain (Maddocks & Oyston, 2008). Several structures of proteins of the LysR family are known; the first structure to be reported was that of the cofactor-binding fragment of the CysB protein from Klebsiella aerogenes (Tyrrell et al, 1997), which revealed several similarities to structures of periplasmic substrate-binding proteins, although the subunit arrangement is different.…”
Section: Introductionmentioning
confidence: 99%